Flagellar Sensillar Equipment of Two Morphologically Closely Related Aphid Hyperparasitoids (Hymenoptera: Figitidae: Alloxysta). Issue 1 (25th January 2016) - Polidori, Carlo; Freitas-Cerqueira, Amanda; Pujade-Villar, Juli; Oliva, Francesc; Ferrer-Suay, Mar
Abstract: The antennal sensillar equipment in the parasitic wasp family Figitidae was analyzed to date only in few species, despite some are associated with crop pests and can have an economic importance. It is the case of the genus Alloxysta, which includes hyperparasitoids of aphids which can potentially reduce effectiveness of primary pest parasitoids. Here we analyzed, through scanning electron microscopy, the diversity, morphology, and distribution of the antennal sensilla in males and females of Alloxysta consobrina (Zetterstedt) and Alloxysta victrix (Westwood), two species with overall very similar morphology. In both species, antennae are filiform and cylindrical, and flagellum was longer in A. victrix . Eight sensillar types have been recognized: four types of sensilla trichoidea (ST-A, ST-B, ST-C, ST-D), sensilla coeloconica, sensilla placoidea, sensilla campaniformia, and sensilla basiconica. ST-A, ST-B, ST-C, and sensilla placoidea were the most abundant types on the antennae and often increased in number and decreased in size toward the tip of antenna. The two species seem to have several differences in their sensillar equipment, possibly in accordance with the different degree of host range. On the other hand, sexual dimorphism is probably due to the different stimuli that have to be correctly processed. The comparison with the other species of Figitidae studied by far showed, at subfamily-level, that variability in sensillar equipment and phylogeny do not agree. This suggests a complex series of morphological changes during evolution of this group. The taxonomic sample should be thus substantially enlarged to disclose possible trends in sensillar equipment evolution in the family.